Multipath Optimised Link State Protocol (OLSR) with Security for Mobile Ad-Hoc Network - Vijaya Bhaskar, Madgula; Ramachandra, GA; Deepika, Y (International Journal of Computer Sciences and Engineering, 2025)
Without the dependence of any infrastructure or central administration to create a temporary network that includes a group of nodes and wireless hosts called as the Adhoc Mobile Network (MANET). Where multipath routing in MANET has been used primarily to transmit data without interruption. Everywhere, the routing technique is primarily considered to ensure the transmission of the message while being used in some protocols. But transmission security is one of the main disadvantages of this network. Therefore, use Secure Multipath Optimized Link State Routing Protocol (SMOLSR), which is a proactive approach to routing protocol-controlled tables, to improve efficiency, which primarily depends on multipoint relay selection (MPR). A new routing protocol for MANET is the progress of the OLSR, which integrates the multi-route strategy and the source routing control scheme. In this protocol, a Dijkstra adaptive algorithm (ADA) has been developed to estimate short-time path based multipath routing and create a control node using the hop in hop authentication model through the bidirectional authentication process (TWA). Initially, find a more limited path using the Dijkstra calculation to create a duplicate topology. In this way, delete the inner and third centers, look for a second more limited path using the Dijkstra calculation. This methodology is called a multi-Dijkstra algorithm. The main objective of the research work defining the quality of the link and the selection of the paths. The TWA process is performed for security to effectively transmit the message. If an interrupt occurs in the source-destination path, it automatically confirms the route to deliver the end-user message without loss of data. The transmitted message is well protected by a TWA process. The performance of the proposed SMOLSR protocol is compared with the many traditional protocols such as OLSR, AOMDV and CA-AOMDV. As a result, the results of the proposed SMOLSR protocol have surpassed that of other protocols.